The Path to Healing: Report of the National Round Table on Aboriginal Health and Social Issues - Canada. Royal Commission on Aboriginal Peoples ([Ottawa]: The Commission, 2013)
This Round Table Report was downloaded from Union of BC Chiefs (http://www.ubcic.bc.ca/) January 7, 2013. Paper copy - CA1 Z1 91A49 Stauffer Library - Documents The Royal Commission on Aboriginal Peoples was estalished on 26 August 1991 by Order in Council P.C. 1991-1597 with the following mandate: "The Commission of Inquiry should investigate the evolution of the relationship among aboriginal peoples (Indian, Inuit and Métis), the Canadian government, and Canadian society as a whole. It should propose specific solutions, rooted in domestic and international experience, to the problems which have plagued those relationships and which confront aboriginal peoples today. The Commission should examine all issues which it deems to be relevant to any or all of the aboriginal peoples of Canada." (P.C. 1991-1597)